The Use of the Diorama in Science Learning about Highlands and Lowlands for Children with Autism Spectrum Disorders - Oom Sitti Homdijah; Rika Aprillia Budiman; Rina Maryanti; Lulu Fikriyah Sholihat; Fandu Fanovanugraha Armindony (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study was to determine the use of dioramas in learning about the highlands and lowlands for children with autistic spectrum disorders. This learning is delivered using diorama media so that children can imagine the actual environmental conditions. The method used is a single-subject method with a pretest-posttest research design. The results of this study will be reviewed from changes in students' knowledge after being given learning using diorama. Data collection techniques will be carried out through pretest before learning and posttest after learning. The result of this research is an increase in knowledge about the highlands and lowlands. it can be seen from the results of the post-test students who experienced an increase in the average value of 45. This is because the diorama learning media is interesting and can stimulate the focus of children with autism spectrum disorders. The results of this study are expected to be a solution for teachers in teaching students about highland and lowland material, especially for children with autism spectrum disorders.